The Impact of Food Bioactives on Health in vitro and ex vivo models - Verhoeckx, Kitty; Cotter, Paul; López-Expósito, Iván; Kleiveland, Charlotte; Lea, Tor; Mackie, Alan; Requena, Teresa; Swiatecka, Dominika; Wichers, Harry (Springer International Publishing : Imprint: Springer, 2015)
This book describes in vitro and ex vivo models that can be employed to investigate effects of digested food products on the GIT, or specific components thereof. Many such models exist and include, for example, those used to study digestion and fermentation in the small and large intestine, to investigate absorption (e.g. Ussing chamber, epithelial cell systems), and to research the immune and enteroendocrine responses (e.g. macrophages, dendritic cells, co-cultures). In each case, these respective assays and models are discussed, and tips and tricks concerning their proper use are given. The Impact of Food Bioactives on Health: In Vitro and Ex Vivo Models is an asset to researchers wishing to study the health benefits of their foods and food bioactives of interest. The book highlights which in vitro/ex vivo assays are of greatest relevance to their goals, what sort of outputs/data can be generated, and highlights the strengths and weaknesses of the various assays. It is also an important resource for under-graduate students in the 'food and health' arena.